(3GdEHJgGL TQM GdefgGL ddfhhis - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s; (3Gdfhhj,J (B676 (3g` s
(3ChdgG (B:s
(3cJGH GdfcGM s
(3BNQgG (B:s
(3BNQ HGH GdfcGM GdeTJQc jJdhg ai GdPi jdjI HGH GdNjGQ hGdCYaGa hfcGM GdYHO s
(3fSNI NGeSIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs